(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The Panchayats are expected to play an important role inrural development in India, particularly after independence. Plan documents ofboth the central and state governments and various committees have emphasizedthe importance of these bodies in the polity. Five-year plans, specially thesecond five-year plan, laid special emphasis on the role of Panchayats in ruraldevelopments. Overall development of country is the main objective ofIndian government since its independence. Earlier the main thrust fordevelopment was laid on Agriculture, Industry, Communication , Education, Healthand Allied sectors but soon it was realized that the all-round development ofthe country is possible only through the development of rural India. RuralDevelopment includes measures to strengthen the democratic structure of societythrough the Panchayati Raj Institutions (PRIs). It also includes measures toimprove the rural infrastructure, improve income of rural households anddelivery systems pertaining to education, health & safety mechanisms.Government of India has taken many steps to develop rural India and for thisDepartment of Rural Development has been setup under the control of Ministry ofRural Development.